On the problem of forming the readiness of teachers for pedagogical activity with children left without parental care - Stukalenko, Нина; Chernenko, Юлия (Рroblems of engineering and professional education, 2023)
In this article, the authors revealed the main directions for solving the problems of preparing teachers working with children without parental care for pedagogical work.